2020
DOI: 10.21608/ejh.2020.20059.1206
|View full text |Cite
|
Sign up to set email alerts
|

Possible Ameliorating Role of Ascorbic Acid on Intestinal Changes Induced by Acrylamide in Adult Female Albino Rats and Their Offsprings

Abstract: Background: Acrylamide (ACR) is a naturally occurring, widely used compound. Ingestion of large amounts of ACR underlies several health concerns and teratogenicity. Ascorbic acid (vitamin C) is a strong reducing agent greatly used to clean free radicals. This study investigated the morphometric, histological, immunohistochemical and biochemical disturbances induced by acrylamide (10 mg/kg/day) via gavage in the intestine of rat mothers and their offsprings. As well as, the protective role of ascorbic acid (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
4
0
3
Order By: Relevance
“…All kits were supplied by Qiagen (Valencia, CA). All samples were assessed in triplicate to confirm the reproducibility and accuracy of the obtained results (Aboregela et al, 2020; Kassab et al, 2020). The primers were designed according to (Al‐Rasheed et al, 2016), as shown in Table 1b.…”
Section: Methodsmentioning
confidence: 99%
“…All kits were supplied by Qiagen (Valencia, CA). All samples were assessed in triplicate to confirm the reproducibility and accuracy of the obtained results (Aboregela et al, 2020; Kassab et al, 2020). The primers were designed according to (Al‐Rasheed et al, 2016), as shown in Table 1b.…”
Section: Methodsmentioning
confidence: 99%
“…PBS kept kidney samples were homogenized in ice-cold 0.1 M Tris-HCl buffer at pH 7.4. Centrifugation of the homogenate at 3,000 rpm for 15 minutes at 4°C was done and the resultant supernatant was isolated for detection of Malondialdehyde (MDA) and Reduced glutathione (GSH) levels [ 35 ]. The pellets were extracted and stored at −20°C [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tinggi vili normal mencit adalah 333,25±45,25 μm (Hidayat et al, 2021), dan tinggi vili usus halus mencit adalah 288,95±7,73 μm (Zou & Zheng, 2013). Tinggi vili normal duodenum mencit adalah 356,58±21,21 μm (Aboregela et al, 2020). Tinggi vili pada kelompok K3 menunjukkan bahwa ekstrak daun kelor LD100 efektif mengurangi peradangan usus sehingga terjadi penyembuhan luka dan perbaikan struktur vili duodenum.…”
Section: Hasil Dan Pembahasanunclassified
“…Penebalan lapisan mukosa duodenum dari ketiga kelompok perlakuan berada di atas kisaran normal tebal mukosa duodenum mencit. Tebal mukosa normal duodenum mencit berkisar antara 342,32-412,85 µm (Aboregela et al, 2020). Penebalan mukosa duodenum setiap kelompok perlakuan terjadi karena adanya peradangan akibat infeksi cacing cestoda.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation